2008
DOI: 10.1111/j.1468-5906.2008.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Relationship Between Religious and Paranormal Constructs

Abstract: Several decades worth of research have produced mixed results concerning the relationship between beliefs in religious and paranormal phenomena. While this previous work focused on the explicit measurement of these beliefs, these studies focused on a new level of analysis. Specifically, what is the implicit relationship between religious and paranormal constructs? In Study 1, participants completed a version of the Implicit Association Test (IAT) to assess the association between religious and paranormal stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…On the whole, the results of Study 3 are consistent with the conclusion that traditional Chinese religions help shape basic traditional beliefs, as well as the conclusion that Christians are less prone to endorse paranormal beliefs than the other sampled groups. The latter result is also consistent with previous studies (Hergovich, Schott, et al., ; Mencken et al., ; Orenstein, ; Rice, ; Shiah et al., ; Weeks et al., ). As in Study 2, the Study 3 results support Cohen and Hill's theory.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On the whole, the results of Study 3 are consistent with the conclusion that traditional Chinese religions help shape basic traditional beliefs, as well as the conclusion that Christians are less prone to endorse paranormal beliefs than the other sampled groups. The latter result is also consistent with previous studies (Hergovich, Schott, et al., ; Mencken et al., ; Orenstein, ; Rice, ; Shiah et al., ; Weeks et al., ). As in Study 2, the Study 3 results support Cohen and Hill's theory.…”
Section: Resultssupporting
confidence: 93%
“…Specifically, it has been shown that greater religious involvement, as defined by church attendance (Orenstein, ) or a Christian affiliation (Hergovich, Schott, et al., ), is strongly associated with lower paranormal belief. Thus, we conclude that greater involvement with Christianity does not necessarily lead to belief in the paranormal (Rice, ; Weeks, Weeks, & Daniel, ), and that the direction of the correlation likely depends on whether or not the religion one practices is Christianity (Mencken, Bader, & Kim, ).…”
mentioning
confidence: 76%
“…Those who strictly adhere to conventional Christian beliefs are less likely than the general population to believe in non‐Christian super‐empirical beliefs (Baker and Draper 2010; Stark 2008). However, among those whose adherence to conventional Christian belief is less strict, there is a positive association between Christian and other super‐empirical beliefs, perhaps due to a preference for or against super‐empirical explanations (Baker and Draper 2010; Weeks, Weeks, and Daniel 2008).…”
Section: Hypothesizing Religious Changein Collegementioning
confidence: 99%
“…Yet it is certainly possible to subject the idea of such bracketing to a genealogical analysis that places the bracketing within the context of a separation in the West and in modernity between religious knowledge and scientific knowledge and between religious practice and secular practice. This becomes evident when we see the conflation of religious belief with belief in supernatural agents, paranormal phenomena, and superstition (Weeks, Weeks, and Daniel 2008).…”
Section: Resultsmentioning
confidence: 99%